Morphological and ecological peculiarities of checker tree mountain ash (Torminalis glaberrima) plants and biochemical composition of its fruits - МоskаlеtsТ. Z.; VоvkоhоnА. H.; BаrаtY. М.; KnyazyukО. V.; Verheles, P. N. (Regulatory Mechanisms in Biosystems, 2020)
The selection and comparative study of new forms of the Red Book species checker tree mountain ash (Torminalis glaberrima (Gand.) Sennikov & Kurtto) were conducted on the basis of generalizing the literary data and expeditionary research on the natural and local gene pool of the above-mentioned plant. Information was presented about the peculiarities of the selection and valuable forms of the checker tree concerning the indices of vitality and morphology in the Central, South-Western, and Western Forest-Steppe of Ukraine. These forms appeared to be characterized by high vigour (over 30–40 cm), large size and mass of the fruits (1.7–2.4 g), their increased nutritional value, high ecological plasticity and ornamentality (crown shape, leaf colouration and shades during the growing season). Taking into consideration the ornamental characteristics, the selected forms are rather promising in landscape construction and phytodesign as complementary elements of oak-beech, oak-hornbeam and other species associations, as well as green corridors of the ecological network. This will contribute to the restoration and preservation of this rare species, thus facilitating restoration, spreading and conservation of this rare species, thereby increasing the stability of ecosystem components, squares, alleys, nature-conservation territories and enhancing the aesthetic qualities of the gardens when establishing harmonious landscape compositions. The fruits of T. glaberrima are characterized as raw material for processing and manufacturing of medicinal preparations and food products. The biochemical analysis of the checker tree mountain ash berries has shown that they are characterized by high content of a number of biologically active substances: polyphenolic compounds, flavonoids, vitamin С. The wide use of the checker tree will enable the food and pharmaceutical markets to be supplied with medicinal and fruit raw material by its introduction into new cultivation conditions, namely: into industrial and ornamental horticulture, forestry. The new genotypes of T. glaberrima were selected and are planned to be transferred to the National Centre for the Plant Genetic Resources of Ukraine. That will make it possible to replenish the genetic bank of Ukraine with representatives of the species, which are promising in fruit growing and ornamental horticulture, forestry and nature conservation.